2022
DOI: 10.1007/s10644-022-09458-5
|View full text |Cite
|
Sign up to set email alerts
|

Is there any recovery power for economic growth from green finance? Evidence from OECD member countries

Abstract: This paper investigates the dynamic interactions between green finance, economic growth, and green energy consumption for the Organization of Economic Cooperation and Development (OECD) members. The econometric analysis is conducted on annual data gathered throughout 2010–2020 using different estimation techniques of the Vector Autoregressive model, causality, and co-integration approaches. The main results confirmed a positive bi-directional relationship between GDP and green energy consumption. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…With sufficient funding, renewable energy projects can be implemented on a larger scale and at a faster pace, contributing to the global transition to cleaner energy sources. A number of research papers support this argument by providing evidence that green bonds significantly foster renewable energy production [19,22,[72][73][74]. In particular, green bonds increase wind and hydro-energy consumption in OECD countries [62].…”
Section: Diversification Of Investmentsmentioning
confidence: 95%
See 2 more Smart Citations
“…With sufficient funding, renewable energy projects can be implemented on a larger scale and at a faster pace, contributing to the global transition to cleaner energy sources. A number of research papers support this argument by providing evidence that green bonds significantly foster renewable energy production [19,22,[72][73][74]. In particular, green bonds increase wind and hydro-energy consumption in OECD countries [62].…”
Section: Diversification Of Investmentsmentioning
confidence: 95%
“…A mutual connection between the volume of green bond and the usage of renewable energy can be observed in OECD countries. The previous research demonstrated that the existence and development of green bonds as financial instruments and well-developed regulatory guidelines on the field perform an important and affirmative role in encouraging investment in renewable energy [22,75]. Nevertheless, oil price volatility and geopolitical risk have a contrary effect.…”
Section: Diversification Of Investmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of global warming and environmental degradation, how to achieve green economic recovery has also attracted wide attention. Among them, many studies explore effective paths for green economic recovery from the perspective of green transformation of financial industry, and find that green finance can increase investment in clean energy development projects (Abbas et al 2020 ; Taghizadeh-Hesary 2022 ; Huang et al 2022 ), reduce energy intensity, and improve energy efficiency (Huang et al 2022 ; Guo et al 2022 ) and energy poverty alleviation (Zhao et al 2022 ) to achieve eco-friendly growth and promote green economic recovery.…”
Section: Introductionmentioning
confidence: 99%